Efficacy and safety of combined loratadine and mometasone furoate therapy in allergic rhinitis patients - Yong, Hui; Di, Lingling; Wang, Zhikai; Yang, Jing; Yang, Pei; Gao, Xiaoping (Frontiers in Immunology, 2025)
ObjectiveThis study seeks to assess the effectiveness and safety of a combination treatment involving loratadine and mometasone furoate for patients suffering from allergic rhinitis (AR). Additionally, it explores the risk factors contributing to treatment failure, providing a theoretical basis for identifying safer and more effective AR treatments.MethodsA prospective study was carried out between January 1, 2021, and April 1, 2023, involving 116 patients with allergic rhinitis (AR) who were treated at our outpatient clinic. Participants were randomly divided into two groups: the control group (n=58), which received loratadine alone, and the study group (n=58), which received a combination of loratadine and mometasone furoate. Outcome measures included nasal symptom scores and serological markers, assessed before and after the treatment period. The effectiveness of the treatment was assessed using nasal symptom scores.ResultsPost-treatment assessments showed that both nasal symptom scores and serological markers were significantly lower in the study group compared to the control group (P<0.05). Additionally, the overall response rate was markedly higher in the study group (P<0.05). There were no significant differences in the total incidence of adverse reactions between the two groups (P>0.05).ConclusionThe combination of loratadine and mometasone furoate effectively alleviates clinical symptoms in patients with allergic rhinitis while demonstrating a favorable safety profile, making it a promising option for clinical use.